1986
DOI: 10.1038/bjc.1986.171
|View full text |Cite
|
Sign up to set email alerts
|

Survival of mice with NC carcinoma is unchanged by drugs that are thought to inhibit thromboxane synthesis or increase prostacyclin formation

Abstract: Summary Mice transplanted with NC carcinoma were treated with the thromboxane synthetase inhibitor dazmegrel (UK38485) or with nafazatrom (BAY G 6575), a compound that is reported to increase prostacyclin formation. Some experiments included the cytotoxic drugs methotrexate and melphalan. The tumours were excised under anaesthesia on day 14 or day 21 after transplanation, and weighed; some were extracted for prostanoids which were measured by radioimmunoassay. Mouse survival time was determined up to day 121, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Nevertheless, our findings are weak evidence against Honn's hypothesis. They are consistent with our finding that the thromboxane synthetase inhibitor dazmegrel reduced mouse serum TXB2 and increased the 6-keto-PGF1,, but had no effect on the survival of mice bearing NC tumours (Stamford et al, 1986). Similarly, recent work in breast cancer patients demonstrated that the TXB2:6-keto-PGF1, ratio in the systemic circulation is not an indicator of malignancy or metastasis (Nigam et al, 1985).…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, our findings are weak evidence against Honn's hypothesis. They are consistent with our finding that the thromboxane synthetase inhibitor dazmegrel reduced mouse serum TXB2 and increased the 6-keto-PGF1,, but had no effect on the survival of mice bearing NC tumours (Stamford et al, 1986). Similarly, recent work in breast cancer patients demonstrated that the TXB2:6-keto-PGF1, ratio in the systemic circulation is not an indicator of malignancy or metastasis (Nigam et al, 1985).…”
Section: Discussionsupporting
confidence: 80%
“…Vasodilator, anti-aggregatory prostacyclin (PG12) and vasoconstrictor, pro-aggregatory thromboxane A2 (TxA2) are especially important in this regard, since their balance may determine, at least partly, the potential of some cancers to grow and spread. This theory has been supported by some studies (Honn & Meyer, 1981Honn et al, 1983a, but also disputed by other data (Stamford et al, 1986). That prostaglandins and prostanoids may be of significance for tumour behaviour gains support from the data that prostaglandin synthesis inhibitors increase the survival time of mice transplanted with mammary carcinoma (Bennett et al, 1982).…”
supporting
confidence: 47%
“…It is generally thought that PGI2 or its dominance over TxA2 should prevent metastasis (Honn et al, , 1983b, but this theory has also been disputed (Stamford et al, 1986). The picture may be partly unclear due to difficulties in assessing PGI2 and TxA2 production in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…TXS has also been shown to be involved with renal cell carcinoma metastasis. Early in-vivo studies with TXS inhibitors have failed to report any beneficial effects on metastasis or spread to the lymph nodes [169]. However, when used in combination with a TP antagonist, TXS inhibitors have been found to inhibit metastasis formation from tail vein injected B16a cells, as well as spontaneous metastasis formation from subcutaneous B16a and Lewis lung carcinoma tumors [162].…”
mentioning
confidence: 99%